Existential Anxiety, Personality Type, and Therapy Preference in Young Adults. (November 2020) - Shumaker, David; Killian, Kathleen; Cole, Courtney; Hruby, Adela; Grimm, Julia
The current study examines the relationship between existential anxiety (EA), personality traits, and therapy preference in a sample of young adults. EA is thought to be universal human experience, yet no published research has been conducted on whether certain personality traits predict higher levels of EA. Males and females ( N = 69) aged 18 to 25 years completed several self-report measures, including a measure of EA, five-factor personality traits, and therapy preference (insight- vs. action-oriented). Pearson correlation coefficients and linear regression analyses were conducted to determine the relationship among the constructs of interest. Results indicate a significant positive correlation between Neuroticism as measured by the NEO-Five Factor Inventory and EA. The Neuroticism N4 Self-Consciousness subscale showed the strongest association with EA. There was no relationship between therapy preference and EA. The results suggest that individuals with personality types characterized by elevated levels of shyness, guilt, and inferiority may be more likely to experience elevated EA. Experiencing higher levels of EA does not seem to affect therapy preference. These findings have important implications for clinicians treating young adults who present with internalizing symptoms.